KONSEP KEPEMIMPINAN PROFETIK - Elitya Rosita Dewi; Chechen Hidayatullah; Dwi Oktaviantari; Maulidya Yuniar Raini (Universitas Muhammadiyah Tapanuli Selatan, 2020)
This study is motivated by the nature of human beings born on the earth as khalifatu fi al-ard or as a leader. In this case, humans are expected to not only be their own leaders but also be leaders in managing, maintaining and managing the earth properly in all aspects of life. However, in the midst of this distribution era, this did not happen. This happens because the current development is so fast and advanced. The main key in this case is the choice or application of leadership models. Basically, the leadership model is diverse, but there is an interesting leadership model to study, namely prophetic leadership. To get data relevant to this problem the author uses descriptive analysis method, namely by providing a clear picture of the concept of prophetic leadership which includes, definitions, principles, nature and types of prophetic leadership. The results of the study show that this leadership model is ideal for implementation in daily life, because this model, was first applied by the Prophets of his time. In addition, the attributes of the Prophet also inspire leadership. Thus, it is expected that leaders can uphold these traits so that they can become good role models in all aspects of life both in society, nation and country.